Age‐related reference values for the pediatric Scale for Assessment and Rating of Ataxia: a multicentre study. (17th August 2017) - Lawerman, Tjitske F; Brandsma, Rick; Burger, Huibert; Burgerhof, Johannes G M; Sival, Deborah A; ,
Abstract : Aim: For reliable assessment of ataxia severity in children, the Childhood Ataxia and Cerebellar Group of the European Pediatric Neurology Society aimed to validate the Scale for Assessment and Rating of Ataxia (SARA) according to age. Method: Twenty‐two pediatric ataxia experts from 15 international institutions scored videotaped SARA performances in 156 typically developing children (4–16y: m/f=1; 12 children per year of age; including nine different nationalities). We determined age‐dependency and reliability of pediatric SARA scores by a mixed model. Results: In typically developing children, age was the only variable that revealed a relationship with SARA scores ( p <0.001). The youngest children revealed the highest scores and the highest variation in scores (<8y; p <0.001). After 11 years of age, pediatric scores approached adult outcomes. The interobserver agreement of total SARA scores was substantial with an intraclass correlation coefficient of 0.63 (95% confidence interval 0.56–0.69; p <0.001). Interpretation: In typically developing European children, both SARA scores and interobserver agreement are age‐dependent. For reliable interpretation of pediatric SARA scores, consideration of the underlying test construct appears prudent. These data will hopefully contribute to a correct and uniform interpretation of longitudinal SARA scores from childhood to adulthood. What this paper adds: Pediatric Scale for Assessment and Rating of Ataxia (SARA) scores are age‐related. The SARA is reliably applicable in children older than 8 years. SARA scores appear less reliable in children younger than 8 years. This manuscript provides age‐related predictive SARA scores for children. This article is commented on by Streiner on pages994–995 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations.